1980
DOI: 10.1111/j.1540-4560.1980.tb02021.x
|View full text |Cite
|
Sign up to set email alerts
|

Complexity of Life Style and Maintenance of Intellectual Abilities

Abstract: Results of longitudinal studies of intellectual abilities show significant individual variation in maintenance or decrement of such functions throughout adult development. The Life Complexity Inventory (LCI) was designed as a questionnaire to investigate those variables present in the day-to-day experience of adults that might relate either to stability or decline of intellectual ability. The LCI was completed by 140 subjects ranging in age from 40-88 years, whose intellectual and personality functioning had b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(75 citation statements)
references
References 19 publications
6
69
0
Order By: Relevance
“…These group-equivalent longitudinal decline patterns replicate cross-sectional findings at T 1 (Lindenberger & Baltes, 1997) and are consistent with earlier longitudinal findings (e.g., Carmelli, Swan, LaRue, & Eslinger, 1997;Gribbin, Schaie, & Parham, 1989;Hultsch et al, 1998;Schaie, 1996;Siegler, 1983; but see Albert et al, 1995;Deary et al, 1998;Kohn & Schooler, 1978, 1983.…”
Section: Covariates Of Intellectual Functioning In Very Old Agesupporting
confidence: 79%
“…These group-equivalent longitudinal decline patterns replicate cross-sectional findings at T 1 (Lindenberger & Baltes, 1997) and are consistent with earlier longitudinal findings (e.g., Carmelli, Swan, LaRue, & Eslinger, 1997;Gribbin, Schaie, & Parham, 1989;Hultsch et al, 1998;Schaie, 1996;Siegler, 1983; but see Albert et al, 1995;Deary et al, 1998;Kohn & Schooler, 1978, 1983.…”
Section: Covariates Of Intellectual Functioning In Very Old Agesupporting
confidence: 79%
“…Nevertheless, there may be certain changes in coping style and motivational structure in response to either biological aging, changes in health or more generalized social-psychological circumstances (Neugarten et al, 1964;Shanan & Jacobowitz, in press). Despite a stereotypic tendency among laymen and even some educators to view older people in simple, stilted terms, research has consistently demonstrated the heterogeneity of this group in terms of social background (Guillemard, 1981;Sagiv & Shanan, 1981), cognitive traits (Schaie, 1979;Willis & Baltes, 1980), personality characteristics (Shanan & Jacobowitz, in press;Thomae, 1980), and in general patterns and styles of development and aging (Gribbin, Schaie, & Parham, 1980;Mass & Kuypers, 1974;Thomae, 1976). There is also accumulating evidence that the extent and nature of this diversity changes in response to changing social circumstances.…”
Section: The Princess and The Frog: Psychology Challenges A Stereotypementioning
confidence: 97%
“…Demographic Measures-Individual characteristics of age, education, gender, marital status, and ethnicity were obtained with the demographic portion of the Life Complexity Inventory (Gribbin, Schaie, & Parham, 1980).…”
Section: Predictor Domains and Measuresmentioning
confidence: 99%